James A. Bourland papers - Bourland, James A., 1801-1868.
Correspondence, orders, muster rolls, invoices, and other papers relating to the command and operations of a regiment of Texas State troops in the Red River Valley during the Civil War and on the Texas-Cherokee Nation frontier.
Available on microfilm
Army officer.
Collection material in English.
Keywords: Red River Valley (Tex.-La.) -- History; United States -- History -- Civil War, 1861-1865.; Texas -- History -- Civil War, 1861-1865.; Cherokee Indians; Army officers